Analytical perspectives on varieties of clientelism. Issue 1 (2nd January 2020) - Yıldırım, Kerem; Kitschelt, Herbert
ABSTRACT: This article explains the varieties of clientelistic vote exchange in contemporary electoral democracies. It distinguishes two commonly recognized modes of exchange according to their capacity to overcome the problem of opportunism – relational clientelism and spot-market "vote buying" clientelism – and relates them to attributes along which clientelistic varieties have been distinguished. It develops a metric of clientelistic profile differences that characterize parties' choices of clientelistic strategies and advances hypotheses about the conditions under which parties pursue different strategies. Drawing on an 88 country/506 party expert survey of clientelistic practices, more relational politics thrives in middle-income countries with simultaneously more programmatic competition. But there is also intra-country variance according to party capabilities: Parties with more formal organizational reach, slight less reliance on external local notables, and government incumbency deploy more relational clientelism, net of parties' electoral size or ethnocultural base. Even once all of these differences are accounted for, parties in Sub-Saharan Africa rely more on spot-market clientelism than those of any other global region. Unmeasured variables – such as state capacity and party institutionalization, as well as the persistence of traditional tribe-based modes of social coordination that endow polities with order and stability may account for the more ephemeral character of clientelism in this region.